An Integrated Framework for Digital Immersive Experiences in Cultural Heritage Presentation - Nikolova, Evgeniya (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This study presents an integrated conceptual framework for digital immersive experiences in cultural tourism, consisting of technological, cultural, behavioral, and management layers. The framework systematically connects these layers through dynamic feedback loops, focusing on cultural authenticity, institutional accountability, and measurable social, educational, and tourism impacts.